The Effect of WWJD Sport Sponsorship on Klaten City Psik on WWJD (What Would Jo Do) Sport Product Purchasing Decisions - Fabilla Hanindinta; Said Junaidi (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
This research aims to determine whether sponsorship of PSIK Kota Klaten influences the decision-making process for purchasing WWJD Sport products. The research method used is quantitative with a survey approach through the distribution of questionnaires to 99 respondents who are fans of PSIK Kota Klaten. The data analysis technique in this study uses simple linear regression by processing the data with the SPSS 26 application. Based on the results of the statistical test, it shows that the sponsorship variable has a positive and significant effect on the purchase decision variable, where the t_calculated value of the sponsorship variable is 13.407, which is greater than the t_table value of 1.66088, and has a significance level of 0.000, which is less than 0.05. This indicates that the sponsorship variable has a positive and significant impact on the purchasing decision of WWJD Sport products.